Prevalence of the BRAFV600E mutation in Greek adults with Langerhans cell histiocytosis. (18th August 2022) - Stathi, Dimitra; Yavropoulou, Maria P.; Allen, Carl E.; Abhyankar, Harshal; Scull, Brooks; Tsoli, Marina; Andreakos, Evangelos; Kaltsas, Gregory; Makras, Polyzois
Abstract: Langerhans cell histiocytosis (LCH) is a rare inflammatory myeloid neoplasia with a broad spectrum of clinical manifestations. The activation of the MAP kinase pathway plays an integral role in its pathogenesis with genetic alterations found in the majority of cases that most frequently involve a somatic mutation of the oncogenic BRAF V600E variant. In this study we investigated the prevalence of the BRAF V600E mutation and its clinical relevance in adult Greek patients with LCH. Among 37 patients studied, the BRAF V600E mutation was identified in 12 out of 31 (38.7%), whereas in six patients (19.3%) the results were in conclusive. The presence of the mutation did not correlate with age at diagnosis, organ involvement, disease extent, response to initial treatment, development of diabetes insipidus and relapse risk. In our series the prevalence of the BRAF V600E mutation is at the lower range of the relative percentage found in children, but in line to that obtained in previous studies of adult patients with LCH that have found an up to 50% prevalence of the BRAF V600E mutation in these patients. Further studies with a larger number of adults are needed to identify the exact prevalence of mutations in the RAS-RAF-MEK-ERK pathway and their role on clinical parameters and disease outcomes. Supplemental data for this article is available online at https://doi.org/10.1080/08880018.2022.2029988 .